Strengthening the Image of Islamic Schools Through the AIDA Approach: The Role of Public Relations in Engaging the Community - Tantowi, Ahmad; Subchan, Ali; Munadirin, Ahmad; Kadarismanto, Kadarismanto; Muslim, Rifqil (JURNAL AL-TANZIM, 2023)
This research aims to reveal the strategy of public relations in building the image of Madrasah. The research was conducted at Madrasah Aliyah NU 05 Gemuh, using a qualitative approach and triangulation techniques. Data collection was carried out through interviews, observations, and field observations. Sources of informants involved school principals, public relations, teachers, and student parents. The research results show that the public relations manager's strategy in building the Madrasah image involves the "Madrasah Greets" program. This approach involves understanding the internal and external conditions of the Madrasah, which is adopted through the Aida theory. Madrasah Greeting is implemented with steps such as understanding the image of the Madrasah from the perspective of attention, public interest, desire, and action. The next step is the implementation of Madrasah consistency and, finally, the Madrasah control program. The implications of this research are the realization of quality Madrasah capable of meeting the educational needs of the community, improving the quality of public education, making Madrasah a center for innovative and creative learning activities, as well as increasing confidence in the existence of Madrasah and eliminating arguments as a second option.